Isolation, characterization and modification of zerumbone from zingiber zerumbet - Mohamad Noor, Nur Farhanah (Chemistry Department, Faculty of Science, 2016)
Zingiber zerumbet Smith belongs to Zingiberaceae family. The most important part of this plant is its rhizomes which have been associated with variety of medicinal uses. Rhizome of the Zingiber Zerumbet Smith is pale yellow with pungent smell and used as traditional medicine in relieving stomach ache, as a diuretic, and when macerated in alcohols are regarded as a tonic and depurative. Hydrodistillation of the rhizome of Zingiber zerumbet yield essential oil with five major compounds which are zerumbone (79.79%), α-humulene (6.85%), camphene (1.04%), caryophyllene oxide (1.36%), and (1R,3E,7E,11R)-1,5,5,8-tetramethyl-12-oxabicyclo-9,1,0-dodeca-3,7-diene (3.24%). The soxhlet extraction method of the rhizome using n-hexane as solvent yielded pale yellow extract crude (8.45 g, 1.69%). Recrystallization of the crude yielded zerumbone as white crystal solid (0.191 g, 2.26%). The zerumbone undergo reactions with m-CPBA in dichloromethane to give zerumbone epoxide (152 mg, 89.91%). Both zerumbone and zerumbone epoxide were characterized using 1H and 13C NMR spectroscropy.